2016
DOI: 10.3340/jkns.2016.59.6.615
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcomes of Post-Fusion Lumbar Flatback Deformity with Sagittal Imbalance

Abstract: ObjectivesTo review surgical results of post-fusion lumbar flatback treated with pedicle subtraction osteotomy (PSO) or Smith-Petersen osteotomies (SPOs).MethodsTwenty-eight patients underwent osteotomies. Radiological outcomes by sagittal vertical axis (SVA), and pelvic tilt (PT), T1 pelvic angle (T1PA), and pelvic incidence (PI)-lumbar lordosis (LL) at preoperative, postoperative 1 month, and final were evaluated. Oswestry Disability Index (ODI), visual analog scale (VAS) score of back pain/leg pain, and Sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…It is noteworthy that the subscale of self-image was improved the most, whereas functional category the least, in the present study. These findings are also consistent with most previous literatures 11,22,23) , possibly reflecting the double sidedness of the deformity correction surgery including long level instrumentation.…”
supporting
confidence: 93%
“…It is noteworthy that the subscale of self-image was improved the most, whereas functional category the least, in the present study. These findings are also consistent with most previous literatures 11,22,23) , possibly reflecting the double sidedness of the deformity correction surgery including long level instrumentation.…”
supporting
confidence: 93%
“…Simon et al found that less lordosis was associated with better quality of life because these patients also had a lower pelvic incidence and therefore better sagittal balance (27). In a Korean study, patients with SVA >5 cm showed a significant improvement in clinical outcome (17). Ploumis et al demonstrated that there was no significant difference between patients with sagittal plane plumbline offset ≥50 mm and those with offset <50 mm with respect to Oswestry and Roland-Morris scores (24).…”
Section: █ Discussionmentioning
confidence: 99%
“…Furthermore, the PI-LL mismatch (LG) after longsegment fusion surgery, particularly for ASD, was found to be associated with residual postoperative symptoms such as low back pain (LBP), lower extremity pain, and numbness [12]. Numerous studies demonstrated a strong correlation between the improvement of sagittal deviation and clinical outcomes after instrumented fusion for various degenerative lumbar spine diseases [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%